Growth Inhibition of Rhizoctonia solani and Its Infection Inhibition on the Rice Seedling by Rice Endophytic Bacteria - Widiantini, Fitri; Yulia, Endah; Fiko, Dinda Sekar (Jurnal Fitopatologi Indonesia, 2022)
Growth Inhibition of Rhizoctonia solani and Its Infection Inhibition on the Rice Seedling by Rice Endophytic Bacteria Rhizoctonia solani is one of the important pathogens in rice plants that can cause blight on seeds, leaves, and leaf sheaths. This rice sheath blight is a serious problem in many rice growing countries, including Indonesia. Controls that rely on the use of synthetic pesticides and resistant varieties often cause new problems, both environmental pollution and the emergence of resistant pathogen populations, so that safer and more environmentally friendly controls are still needed. This study reported the potential of endophytic bacteria from healthy rice plants in inhibiting the growth of R. solani in vitro and their ability to suppress R. solani infection in rice germination. The experiment used a dual culture method between endophytic bacterial strains and R. solani. Observations were made on the growth of R. solani colonies and microscopic mycelium growth. The test was continued by treating the rice seeds using endophytic bacteria. Rice seeds that have been coated with endophytic bacteria were then grown on potato dextrose agar medium that has been overgrown with R. solani. The level of disease blight in seeds showed that almost all of the bacterial strains tested could inhibit the growth of R. solani colonies and also cause malformations in their mycelium. The application of endophytic bacteria to rice seeds also significantly reduced the infection rate of R. solani in rice seeds. Among the bacteria tested, OS7 has the potential to be developed as a biological control agent for rice sheath blight caused by R. solani. Further research on the greenhouse and field scale needs to be done.